2017
DOI: 10.1016/j.jaci.2016.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Early oral immunotherapy in peanut-allergic preschool children is safe and highly effective

Abstract: Background Oral immunotherapy (OIT) is an effective experimental food allergy treatment that is limited by treatment withdrawal and the frequent reversibility of desensitization if interrupted. Newly-diagnosed preschool children may have clinical and immunological characteristics more amenable to treatment. Objective To test the safety, effectiveness, and feasibility of early OIT (E-OIT) in the treatment of peanut allergy. Methods We enrolled 40 children aged 9–36 months with suspected or known peanut alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
269
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(313 citation statements)
references
References 39 publications
18
269
2
2
Order By: Relevance
“…3), which likely corresponds to the reduction of the numbers of IgEproducing cells. This result was concordant with the results based on serum peanut-specific IgE levels (P = 0.034 and 0.62, respectively, in OIT and placebo groups), and also several reports demonstrating that serum peanut-specific IgE levels were significantly decreased by the treatment of OIT [13,21,24,25]. We observed one common IGHE clone among two pre-treated OIT and five pre-treated placebo samples (Supplementary Table 5), but this clone was still retained in the samples after OIT and placebo treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3), which likely corresponds to the reduction of the numbers of IgEproducing cells. This result was concordant with the results based on serum peanut-specific IgE levels (P = 0.034 and 0.62, respectively, in OIT and placebo groups), and also several reports demonstrating that serum peanut-specific IgE levels were significantly decreased by the treatment of OIT [13,21,24,25]. We observed one common IGHE clone among two pre-treated OIT and five pre-treated placebo samples (Supplementary Table 5), but this clone was still retained in the samples after OIT and placebo treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Among them, 12 patients received peanut flour and the remaining 5 patients received a placebo until the final oral food challenges. In this analysis, we focused on IGHA, IGHE, and IGHG, which have been reported to associate with food allergy [13,[21][22][23][24][25]. In the expression analysis using real-time qPCR, we observed the tendency of Table 1 Mapping pattern of BCR reads in a healthy donor Number of reads (%) -not mapped decrease of IGHE expression after OIT compared to before OIT (P = 0.052) but not in placebo group (P = 0.63) (Fig.…”
Section: Bcr Expression and Sequencing Of Oit Samplesmentioning
confidence: 99%
“…Although egg OIT generally uses EW powder [2][3][4], Yanagida et al [8] reported that low-dose (i.e., 1/100-1/32 of a whole egg [62-192 mg of egg protein] in scrambled form once a day) OIT induced sustained unresponsiveness to 1/32 and 1/2 of a whole egg in scrambled form, with no severe symptoms. Vickery et al [11] reported that sustained unresponsiveness was achieved at high rates with OIT, both low-dose (300 mg) and high-dose (3,000 mg) peanut flour once a day, in young peanut-allergic children. However, in an allergic mouse model, the intake of a small amount of allergen did not induce oral desensitization [12].…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent open-label RCT analyzing peanut OIT in a population aged 9 to 36 months [25], patients were randomized to goal maintenance doses of 300 mg/d or 3000 mg/d. In the intentto-treat analysis, 29 of 37 patients (78%) achieved SU 4 weeks after completing treatment, with similar rates in the 300-mg group (85%) and the 3000-mg group (71%) after a median treatment period of 29 months.…”
Section: Peanut Oitmentioning
confidence: 99%